2021
DOI: 10.1136/bmjsem-2021-001161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eating disorders on male team sports players

Abstract: ObjectiveTo determinate the prevalence of EDs in national adult male team sports players.MethodologyAn observational study was conducted with 124 football, rugby, volleyball, handball, water polo, baseball and hockey players ranging between 18 and 55 years old. All subjects signed the informed consent before participating in the study. Data were collected via an online form including four validated questionnaires: The Eating Habits Questionnaire for Athletes, the Eating Attitudes Test (EAT-40), the Eating Diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The comparison between lack of involvement in any sport, practicing an individual sport, and practicing a team one, showed a clear pattern of distribution in sex-based subgroups. This topic is poorly explored in literature and allowed us to integrate different facets of the role of physical activity on mental health [ 24 26 ]. In the study sample, a significant overlap existed between team sports and non-leanness sports (with a higher importance of technical skills), and between individual sports and leanness sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between lack of involvement in any sport, practicing an individual sport, and practicing a team one, showed a clear pattern of distribution in sex-based subgroups. This topic is poorly explored in literature and allowed us to integrate different facets of the role of physical activity on mental health [ 24 26 ]. In the study sample, a significant overlap existed between team sports and non-leanness sports (with a higher importance of technical skills), and between individual sports and leanness sports.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available studies addressing the relationship between physical activity and ED psychopathology are based on the “leanness” vs “non-leanness” sports paradigm [ 23 ]. On the contrary, the “team” vs “individual” sports perspective is under-addressed in representative, non-clinical populations, and it has led to inconclusive or mixed results which warrant further evaluation [ 24 26 ]. In fact, the preference for sedentary behaviours or individual training may indirectly reflect a rise in extrinsic motivations to practice sports, a condition that has been identified as a risk factor for EDs [ 27 ], and the internalisation of appearance ideals may be tied to disordered eating, especially among boys [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of the IOC consensus documents [ 4 , 5 ], research on RED-S and LEA has increased, and the prevalence of LEA is of concern. Recent studies have shown that 45% of female recreational exercisers were at risk of LEA [ 20 ], while another study found a high prevalence of LEA in both male and female elite youth athletes (males, 56%; females, 51%) [ 6 , 21 ].…”
Section: Introductionmentioning
confidence: 99%